2008
DOI: 10.1210/en.2008-1081
|View full text |Cite
|
Sign up to set email alerts
|

Facilitative Glucose Transporter Type 1 Is Differentially Regulated by Progesterone and Estrogen in Murine and Human Endometrial Stromal Cells

Abstract: Embryo implantation is a highly synchronized event between an activated blastocyst and a receptive endometrium. The success of this process relies on the dynamic interplay of estrogen (E(2)) and progesterone (P(4)), however, the details of this interaction are not entirely clear. Recent data implicate E(2) and P(4) in the regulation of glucose utilization by affecting facilitative glucose transporter (GLUT) expression. In this study we examine GLUT1 expression in murine and human endometrial stromal cells (ESC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 36 publications
5
63
3
Order By: Relevance
“…It has also been reported that P 4 directly regulates SCL2A1 expression in endometrial cells (Frolova et al 2009) via its own receptor (Frolova et al 2009), thereby activating the intracellular signalling pathway and enhancing GLUT1 expression levels and translocation to the plasma membrane ). Both studies suggest an opposite function for E 2 , i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that P 4 directly regulates SCL2A1 expression in endometrial cells (Frolova et al 2009) via its own receptor (Frolova et al 2009), thereby activating the intracellular signalling pathway and enhancing GLUT1 expression levels and translocation to the plasma membrane ). Both studies suggest an opposite function for E 2 , i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological changes following ovulation until late in dioestrus (Sonnack 2009) as well as changes in steroid hormone, prostaglandin and cytokine levels have been described to act as local regulatory factors (Engel et al 2005, Kowalewski et al 2008a, 2008b, Papa & Hoffmann 2011. The lifespan of the CL depends on energetic supply (Downing et al 1995), which may be regulated by steroid hormones (Frolova et al 2009): in endometrial cells, progesterone (P 4 ) directly regulates the expression of glucose transporter type 1 (SLC2A1 gene/GLUT1 protein) through its receptor , activating the signalling pathway Akt/PKA/ PRKAA and increasing the expression and translocation of GLUT1 , the most ubiquitously distributed facilitative glucose transporter responsible for taking up glucose at basal conditions (Palfreyman et al 1992). Besides steroid hormones, the hypoxia-inducible factor 1a (HIF1A) has been implicated as a potent inducer of GLUT1 and of its gene SLC2A1 (Takagi et al 1998, Sone et al 2000, Zhao & Keating 2007, Kihira et al 2011, Mattmiller et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the presence of a progesterone receptor antagonist (RU-486), progesterone effect on GLUT1 and glucose uptake is abolished. Thus it appears that the progesterone-induced receptivity by the endometrium is reliant on GLUT1-mediated glucose uptake by the endometrial stromal cells (33).…”
Section: Early Implantation and Embryo Developmentmentioning
confidence: 99%
“…Real-time RT-PCR SYBR green-based real-time RT-PCR was used for quantification of candidate endometrial genes involved in the prostaglandin pathway , associated with preimplantation ruminant pregnancy , associated with embryonic growth (Wathes et al 1998;Frolova et al 2009) and expressed by the early trophoblast (Ushizawa et al 2004) using a Corbett Rotor-Gene 600 instrument with 10-mL reactions containing 5 mL TaKaRa Sybr Premix Ex Taq mix (Takara Bio Inc., Otsu, Japan), 0.1 mM of each primer and 2 mL template. The thermal program included a 1-min incubation at 958C to activate the TaKaRa Ex Taq HS polymerase followed by 40 cycles of 958C for 10 s, annealing temperature of 608C for 15 s and extension at 608C for 20 s with ramp speed 208C s À1 .…”
Section: Progesterone Measurementmentioning
confidence: 99%